A haptic model for virtual petrosal bone milling - Eixelberger, Thomas; Wittenberg, Thomas; Perret, Jerome; Katzky, Uwe; Simon, Martina; Schmitt-Rüth, Stephanie; Hofer, Mathias; Sorge, Martin; Jacobs, Roland; Engel, F; Gostian, Antoniu-Oreste; Palm, Christoph; et al. (Proc’s 17. Jahrestagung der Deut¬schen Ge¬sellschaft für Computer- und Roboterassistierte Chirurgie (CURAC 2018), 2018)
Virtual training of bone milling requires real-time and realistic haptics of the interaction between the ”virtual mill” and a ”virtual bone”. We propose an exponential abrasion model between a virtual bone and the mill bit and combine it with a coarse representation of the virtual bone and the mill shaft for collision detection using the Bullet Physics Engine. We compare our exponential abrasion model to a widely used linear abrasion model and evaluate it quantitatively and qualitatively. The evaluation results show, that we can provide virtual milling in real-time, with an abrasion behavior similar to that proposed in the literature and with a realistic feeling of five different surgeons.<br

Online-Offline Co-Creation - Daiberl, Christofer; Danzinger, Frank; Dinter, Barbara; Hess, Joseph; Höckmayr, Benedikt; Jonas, Julia; Kollwitz, C.; Luzsa, Robert; Putz, Michael; Roth, Angela; Schmitt-Rüth, Stephanie; Wehnert, Peter (2016)

Tools for collaborating and interacting in Living Labs - Perez Mengual, Maximilian; Jonas, Julia; Schmitt-Rüth, Stephanie; Danzinger, Frank (ServDes, 2018)
Living Labs serve as a novel form of collaborating and developing innovation. As interactive, physical settings, they hold several possibilities of facilitating co-creation with diverse stakeholders. Research on tools and methods used in Living Labs is still under development. To contribute to this research, this paper investigates the use of tools for interaction in a Living Lab. A longitudinal exploratory case study on the JOSEPHS® in Nuremberg was applied. This study finds that (1) there are three categories of tools used for integrating visitors, (2) interaction with visitors in a Living Lab depends on the factors time and commitment and (3) tools for different integration types need to be matched to the determinants of interaction. The study contributes to literature on co-creation and interaction in Living Labs by highlighting that visitor roles should not be perceived as fixed user categories, but as the variable result of interaction with applied tools.<br
Keywords: co-creation; living labs; tools; interaction